Social Simulation of Intergroup Conflicts Using a New Model of Opinion Dynamics - Ishii, Akira; Okano, Nozomi; Nishikawa, Masaru (Frontiers in Physics, 2021)
The social identity theory proposed by Tajfel et al. provides insight into how group membership and self-categorization cause intergroup prejudice and discrimination, finally leading to social conflicts. However, unanswered questions remain: under what conditions can an “in-group” and an “out-group” transform conflictual intergroup behavior into a more harmonious relationship and avoid social conflict? Opinion dynamics theory and social simulation are appropriate methods to answer this question. In this study, a new model of opinion dynamics proposed by Ishii is adopted, and we conduct simulations of intergroup conflicts. The new model, along with social simulations, presents how an in-group and an out-group can develop social harmony and avoid social conflict. According to our simulations, when the two groups trust their members 100%, the opinion inside an in-group converges. However, intragroup opinion diverges as trust within the group gets lower. On the other hand, intergroup opinion converges when the intergroup trust is higher than 50%. If intergroup trust is higher than 80%, then the intergroup opinions of the two perfectly overlap. Furthermore, if intragroup trust is 70% and intergroup trust is as low as 50%, the two groups' opinions completely polarize. We also calculated additional cases where intragroup trust was fixed at 70%, but for one-third of an in-group member trust an out-group with various values. Finally, a method to avoid further social crises can be obtained by examining real-world cases of partisan conflicts in recent America.